Efficacy of Schirmer’s Test I and Tear Break Up-Time (TBUT) test among Patients of Type II Diabetes with Dry Eye - Faiza Sharif, Syed Nishat Akram, Hafsa Sharif, Rida Khalid, Arslan Saleem Chughtai, Muhammad Ajmal Chaudhary, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the efficacy of Schirmer’s I test and TBUT test in dry eye changes in type II diabetic patients. Subjects& Methods: In these prospective study 58 (116 eyes) dry eye patients with diabetesmellitus type II patients with minimum duration of 5 year, with BCVA of 6/12 to 6/6. After baseline examination, TBUT Test and Schirmer’s Test I were performed to measure dry eye changes occurred due to DM type II.As the data was not normally distributed therefore Wilcoxon sign rank test were applied using p-value ≤0.05 as significant. Results:In the current study on average duration of diabetes was 5.90±1.17 (Range 5-9)years. 30(50.8%) had 5 years history of diabetes, 15(25.4%) had 6years, 7(11.9%) has 7years, 4(6.8%) had 8years and 3(5.1%) had 9 years history of diabetes. Schirmer's Test I Ocular Dexter (OD) &Oculus Sinister (OS) were 12.90±3.65mm and 12.56±3.23mm. Mean difference was statistically significant (p-value 0.022). Whereas mean TBUT of Ocular Dexter (OD) &Oculus Sinister (OS) were 18.81±6.730 and 19.63±7.083 respectively, the mean difference was not statistically significant (p-value 0.342). Differences between TBUT & Schirmer’s I test of OD and TBUT & Schirmer’s I test of OS were statistically significant (p-value <0.001). Conclusion: This study evaluates that TBUT Test are much significant as compared to Schirmer’s test because they have so much difference in their Mean ± Std. Deviation. Keywords: TBUT Test, Schirmer’s Test I, Diabetes type II, Dry Eye.